Design and Construction of a Stove Using Used Oil - Azzikri , Muhammad Fadhil; Azriadi, Emon; Rusnedy , Hidayati (Journal of Engineering Science and Technology Management (JES-TM), 2024)
The tool design stage uses the help of the AutoCAD application. The next stage is the manufacture of used oil-fueled stoves. Followed by testing the used oil-fueled stove. Based on the results of the two stoves that have been tested above, it is concluded that the time to boil 5 liters of water in a used oil-fired stove is 2 minutes faster than a gas stove, this can be proven in the results, namely the time to boil water in a used oil-fired stove is 7 minutes, while the time it takes to boil water in a gas stove is 9 minutes. The stove that is produced is able to be an alternative when the price of fuel in the form of gas soars so that it can be a solution for cooking with fuel at an affordable price. Researchers need to pay more attention to the selection of stove wall coating materials so as not to conduct excessive heat.